Formation of primary radiation defects in a non-equilibrium silicon structure by electron irradiation. Issue 3 (November 2020) - Bogatov, N; Grigoryan, L; Klenevsky, A; Kovalenko, M; Nesterenko, I
Abstract: Based on numerical simulation, the influence of the position in the band gap of the Fermi quasilevel of electrons on the dependence of the linear generation rate of interstitial silicon, vacancies, divacancies, and disordering regions in silicon irradiated with electrons is analyzed. From the obtained results it follows that, if the quasi-Fermi level of electrons is located in the upper quarter of the band gap and approaches the bottom of the conduction band, then the linear rate of generation of primary radiation defects created by electrons decreases. Consequently, under nonequilibrium conditions caused by a high level of illumination or the passage of an electric current through the n + - p junction in the forward electric bias mode, as well as in the n + -region of silicon, it is possible to differentially vary the concentration of radiation defects when exposed to electrons. The results obtained can find application in the development of new methods for modifying the properties of semiconductor structures.